How We Write: Thirteen Ways of Looking at a Blank Page - Conklin Akbari, Suzanne (punctum books, 2015)
The contributors range from graduate students and recent PhDs to senior scholars working in the fields of medieval studies, art history, English literature, poetics, early modern studies, musicology, and geography. All are engaged in academic writing, but some of the contributors also publish in other genres, includes poetry and fiction. Several contributors maintain a very active online presence, including blogs and websites; all are committed to strengthening the bonds of community, both in person and online, which helps to explain the effervescent sense of collegiality that pervades the volume, creating linkages across essays and extending outward into the wide world of writers and readers.